HUBUNGAN KONSENTRASI DEBU DENGAN SICK BUILDING SYNDROM (SBS) DI BRI CABANG PANGERAN SAMUDERA BANJARMASIN - Jaini, Muhammad; Setyaningrum, Ratna; Fakhriadi, Rudi (Universitas Lambung Mangkurat, 2014)
SBS is phenomenons that sufferred when still working insides a closed work room and air-conditioned room for long time. SBS caused of some free radical. The free radical comes from ultraviolet light radiation, metabolism in body, radiation ion, cigarette smoke, and air with particulatet dust flies or particulatet matter. This study aimed to analyze correlation between dust concentration with SBS at branch BRI Pangeran Samudera Banjarmasin. This study using survey analytic with cross sectional method. The numbers of sample is 34 workers. Dust concentration on floor 3 for location I, II, and III is 15,53μg/Nm3, 2,82 μg/Nm3,dan 24,01 μg/Nm3 and on floor 4 is 8,47μg/Nm3, 4,24 μg/Nm3,dan 5,65μg/Nm .The responden with SBS is 3(8,82%) people. The result analysis with chi square test got p=0,227 (p>0,05). The concluding of this study shown no correlation between dust concentration with SBS Keyword: dust, SBS, Particulatet Matter